Experimental characterization of tensile properties of epoxy resin by using micro-fiber specimens. (December 2016) - Misumi, Jun; Ganesh, Raja; Sockalingam, Subramani; Gillespie, John W
In unidirectional carbon fiber-reinforced plastic laminates, the distance between fibers can varies from submicron to micron length scales. The mechanical properties of the matrix at this length scale are not well understood. In this study, processing methods have been developed to produce high quality epoxy micro-fibers with diameters ranging from 100 to 150 µm that are used for tensile testing. Five types of epoxy resin systems ranging from standard DGEBA to high-crosslink TGDDM and TGMAP epoxy systems have been characterized. Epoxy macroscopic specimens with film thickness of 3300 µm exhibited brittle behavior (1.7 to 4.9% average failure strain) with DGEBA resin having the highest failure strain level. The epoxy micro-fiber specimens exhibited significant ductile behavior (20 to 42% average failure strain) with a distinct yield point being observed in all five resin systems. In addition, the ultimate stress of the highly cross-linked TGDDM epoxy fiber exceeded the bulk film properties by a factor of two and the energy absorption was over 50 times greater on average. The mechanism explaining the dramatic difference in properties is discussed and is based on size effects (the film volume is about 2000 times greater than the fiber volume within the gage sections) and surface defects. Based on the findings presented in this paper, the microscale fiber test specimens are recommended and provide more realistic stress–strain response for describing the role of the matrix in composites at smaller length scales.